Implementing EITI for Impact : A Handbook for Policy Makers and Stakeholders - World Bank (Washington, DC, 2013)
The purpose of this handbook is to provide guidance to stakeholders (including policy makers, industry, and civil society) in countries currently implementing, or seeking to implement, EITI. It provides practical guidance on the measures required to launch and implement EITI successfully. In addition, using the Extractive Industries (EI) Value Chain as an analytical tool, this handbook holistically analyzes the importance of EITI to domestic economies, governance structures, and local populations, and suggests measures to leverage its potential to ensure inclusive growth and sustainable development. To enable the achievement of this goal, this handbook assists EITI-implementing countries in mainstreaming EITI into the good-governance agenda by recommending global good-fit practices, by building on the EITI standards. EITI Principles, Criteria, and Rules inform the contents of this handbook.